Peran MUI dalam Penguatan Demokrasi Indonesia - M Sya’roni Rofii (Jurnal Hukum Islam, 2019)
Indonesia is still considered the nation with the world’s biggest Muslim population highlighting democracy. This predicate results from the impact of the country’s large population followed by the acceptance of the Muslim community toward democracy, which is deemed contrary to religious values in some Muslim countries. The acceptance of democracy situated in Indonesia cannot be separated from the legitimacy of religious authority; it refers to the Indonesian Ulema Council (hereafter, MUI). This religious council plays a pivotal role in ensuring democracy as ‘the only game in town’. The present study seeks to answer (1) what is the contribution of the MUI in strengthening democracy in Indonesia? and (2) how do the MUI leaders endeavor when encountering the political situation in the 2019 election demonstrated by an identity politics struggle which tended to divide the Indonesian Muslim communities? Grounded in qualitative library research, the study applied analytic-descriptive analysis. The findings promote that the MUI significantly contributed to ensure the well-established democratic system in Indonesia through their fatwas. It implies that MUI supports the continuation of fair elections and national stability, tackles a dispute over the Indonesia’s election, and fosters that religion is not merely employed as a political tool.